A rapid evidence review of the effectiveness and cost-effectiveness of alcohol control policies: an English perspective. Issue 10078 (15th April 2017) - Burton, Robyn; Henn, Clive; Lavoie, Don; O'Connor, Rosanna; Perkins, Clare; Sweeney, Kate; Greaves, Felix; Ferguson, Brian; Beynon, Caryl; Belloni, Annalisa; Musto, Virginia; Marsden, John; et al.
Summary: This paper reviews the evidence for the effectiveness and cost-effectiveness of policies to reduce alcohol-related harm. Policies focus on price, marketing, availability, information and education, the drinking environment, drink-driving, and brief interventions and treatment. Although there is variability in research design and measured outcomes, evidence supports the effectiveness and cost-effectiveness of policies that address affordability and marketing. An adequate reduction in temporal availability, particularly late night on-sale availability, is effective and cost-effective. Individually-directed interventions delivered to at-risk drinkers and enforced legislative measures are also effective. Providing information and education increases awareness, but is not sufficient to produce long-lasting changes in behaviour. At best, interventions enacted in and around the drinking environment lead to small reductions in acute alcohol-related harm. Overall, there is a rich evidence base to support the decisions of policy makers in implementing the most effective and cost-effective policies to reduce alcohol-related harm.